Management of plant nutrients for enhancing oil content in oilseed crops - A review (Journal of Oilseed Brassica, 2025)
Nutrient management is an important activity in crop production. Most of the cases, organic and inorganic sources of plant nutrients are advocated for enhancing the nutrient concentration in soil and uptake by plant roots. However, soil physico-chemical properties greatly influenced by the availability of plant nutrients in soil solution. Addition of organic matter through FYM, crop residues, green manuring enhanced the fertilizer use efficiency in most of the soils. In most of the oilseed crops, nutrient management is an important task for improving the soil health parameters and sustainable crop yield. Oilseed crops majorly require nitrogen, phosphorus, potassium, sulfur, calcium, zinc and boron based on the soil test values. Other advance agronomic practices also carried out to enhance the fertilizer use efficiency in oilseed over a period of time. Integrated use of chemical fertilizers with organic sources improved the soil physico-chemical, biological properties in soil in a long run. Soil test based management of plant nutrients are advocating for sustainable oilseed production without compromising the soil and environmental health. In this review, the major plant nutrients role in oilseed production and their efficient management through the best management practices are discussed. It also indicated that the climatic factors also influence the efficiency of plant nutrients during the crop growth. Increasing awareness about the balance application of plant nutrients in oilseed crops is a key activity in nutrient management.